Effect of defocused plane on entrance and exit hole geometry of high grade steel 18CrNi8 during percussion drilling by Nd:YAG millisecond laser system. (13th January 2020) - Nawaz, Saad; Kashif, Muhammad; Abbas, Naseem; Farooq, Muhammad; Farhan, Muhammad; Amjad, Muhammad; Noor, Fahad; Naqvi, Rizwan Ali
Abstract: Modern manufacturing industries prefer laser drilling processes owing to the adequate controlled drilling in comparison with existing alternatives. The presented experimental study mainly accounts defocusing impact along with other technical parameters and optimization of Nd:YAG millisecond pulsed laser drilling; and finally their influence on the entrance and exit holes profile. The key technical parameters such as pulse frequency, pulse width and assisting gas pressure with respect to different defocused focal plane are explored experimentally for the percussion laser drilling of high grade steel 18CrNi8. Experiment results revealed that increase in defocusing distance has caused an increment in hole entrance diameter; however, with different defocusing distance, the entrance diameter increasing rate keep changing. Different trends of increasing and decreasing diameter at entrance and exit are recorded and investigated with respect to work-piece defocusing positions. The defocusing variation of laser beam has been investigated with the hole profile, changing from straight hole to tapered blind hole. Which leads to conclusive and optimized results for obtaining optimal hole profile (at entrance and exit). The optimum parametric combinations for attaining lower heat treatment effects are also discussed for superior hole quality.